A COMPREHENSIVE INFORMATIVE NOTE ON ASCITES - Singh, Navneet; Patyar, Sazal; Chandra Talniya, Naveen (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Ascites impairs both the physical and mental dimensions of quality of life in patients. The patients due to unawareness do not report to medical practitioners in the early stage of disease, and also in few cases, medical practitioners due to lack of adequate expertise face difficulty to ensure the early stage detection for causes of ascites, i.e., due to cirrhosis, cancer, congestive heart failure, mycobacterium tuberculosis, or others. Ascites is a symptom of progression of single disease or multiple diseases. Gross collection of fluid in peritoneal cavity may initiate a series of problems such as spontaneous bacterial peritonitis and an increase in abdominal distension and discomfort and hinder the mobility of the patient and dullness and loss of appetite. In the present review, a detail study over the ecology of ascites has been done with emphasizing on diagnosis by history and physical examination, clinical examination, and imagining techniques followed by management of treatment through general guidelines, and various available therapies are covered.